2017
DOI: 10.1038/s41598-017-04541-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chemical alternation on damage accumulation in concentrated solid-solution alloys

Abstract: Single-phase concentrated solid-solution alloys (SP-CSAs) have recently gained unprecedented attention due to their promising properties. To understand effects of alloying elements on irradiation-induced defect production, recombination and evolution, an integrated study of ion irradiation, ion beam analysis and atomistic simulations are carried out on a unique set of model crystals with increasing chemical complexity, from pure Ni to Ni80Fe20, Ni50Fe50, and Ni80Cr20 binaries, and to a more complex Ni40Fe40Cr2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 62 publications
2
13
0
Order By: Relevance
“…As such, the trend of defect number simulated is comparable to the damage accumulation observed in experiments. The results indicate similar defect evolution between Ni 0.5 Fe 0.5 and Ni 0.8 Cr 0.2 , which is consistent with experimental results [25]. In addition, the lowest defect number in Ni 0.4 Fe 0.4 Cr 0.2 and Ni 0.333 Co 0.333 Cr 0.333 is also in accordance with the available experiments [8,26] 333 , yet the defect evolution in these three alloys is similar.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As such, the trend of defect number simulated is comparable to the damage accumulation observed in experiments. The results indicate similar defect evolution between Ni 0.5 Fe 0.5 and Ni 0.8 Cr 0.2 , which is consistent with experimental results [25]. In addition, the lowest defect number in Ni 0.4 Fe 0.4 Cr 0.2 and Ni 0.333 Co 0.333 Cr 0.333 is also in accordance with the available experiments [8,26] 333 , yet the defect evolution in these three alloys is similar.…”
Section: Discussionsupporting
confidence: 91%
“…However, the original version of the Cr potential leads to instabilities in alloys, and slight modification was made based on the analysis of Anand et al [30]. These potentials have been successfully used to model damage evolution in corresponding alloys previously [8,10,21,24,25].…”
Section: Methodsmentioning
confidence: 99%
“…In order to evaluate qualitatively the evolution of the relative disorder resulting from the Ar-ion irradiation, disorder profiles were extracted from the analysis of RBS/C spectra (these spectra are plotted in Figure S1 of the supplementary material) using an iterative procedure [41], which has been previously used to analyze ion-irradiated SP-CSAs at RT [18,19] and validated in some recent molecular dynamics simulations [42,43]. The obtained disorder profiles for Ar-irradiated Ni (red circles) are illustrated in Figure 1 and compared with those for Arirradiated NiFe (blue triangles) and NiFeCoCr (green squares) single crystals.…”
Section: Resultsmentioning
confidence: 99%
“…nuclear reactor applications), a combination of these improvements is highly desirable, and exploiting the extreme chemical disorder of concentrated alloys may provide a new paradigm for designing structural materials for next-generation nuclear power systems. Over the past few years, pioneering efforts have been devoted to the fundamental understanding of radiation defects in SP-CSAs, mimicking the radiation produced in nuclear reactors using external irradiations with various types of heavy ions at room temperature (RT) [14][15][16][17][18][19] and high temperatures (HT) [20][21][22][23][24][25][26]. The results of these studies have demonstrated that increasing chemical complexity strongly enhances the radiation resistance of these alloys, which has been attributed to sluggish diffusion [27][28][29] and enhanced dynamic annealing of simple defects at early stages during irradiations at RT and HT [2,15,23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation